The Concept of Divine Justice and Mercy in the Prophetic Literature of the Hebrew Bible - OBJANTORO , Enggar; SELI, Emi; JULIANES, Matius (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
This interdisciplinary study, situated at the intersection of Biblical Studies, Cultural Heritage and Indigenous Studies, examines the dynamic interplay between divine justice (mishpat) and mercy (hesed) in the Hebrew prophetic tradition. Focusing on the texts of Amos, Hosea, Isaiah, and Jeremiah, the paper explores how these prophets articulate Yahweh’s dual role as righteous judge and compassionate redeemer within Israel’s covenant framework. Through close textual analysis and historical-critical methodology, the study demonstrates how prophetic oracles of judgment against social oppression (Amos 5:24) and religious hypocrisy (Isaiah 1:17) coexist with profound assurances of restorative mercy (Hosea 11:8-9; Jeremiah 31:20). The research reveals that the prophets’ theological genius lies in their ability to hold these seemingly contradictory divine attributes in creative tension, presenting them not as oppositional forces but as complementary aspects of covenantal fidelity. The paper makes three significant contributions: First, it shows how the prophetic understanding of justice transcends mere retribution, serving instead as a necessary precursor to restoration (Jeremiah 31:31-34). Second, it highlights the enduring cultural relevance of this justice-mercy dialectic, particularly for Indigenous approaches to restorative justice and contemporary debates about moral accountability. Third, it argues that the prophets’ vision of divine-human relationship offers a transformative paradigm for modern discussions of social ethics, where justice and mercy must operate in dynamic equilibrium. By examining this ancient theological tension through multiple disciplinary lenses, the study demonstrates how the prophetic tradition continues to inform and challenge contemporary conceptions of justice, reconciliation, and covenantal community.